2017
DOI: 10.2807/1560-7917.es.2017.22.14.30504
|View full text |Cite
|
Sign up to set email alerts
|

Performance of influenza case definitions for influenza community surveillance: based on the French influenza surveillance network GROG, 2009-2014

Abstract: International case definitions recommended by the Centers for Disease Control and Prevention (CDC), the European Centre for Disease Prevention and Control (ECDC), and the World Health Organization (WHO) are commonly used for influenza surveillance. We evaluated clinical factors associated with the laboratory-confirmed diagnosis of influenza and the performance of these influenza case definitions by using a complete dataset of 14,994 patients with acute respiratory infection (ARI) from whom a specimen was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
93
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 21 publications
13
93
1
Order By: Relevance
“…Cough was the most frequently reported symptom, associated with IV, RSV and HMPV detections, as expected [1,3,17]. Presence of dyspnoea was associated with RSV infection and absence of dyspnoea was related to IV detection, as previously reported [16]. This is consistent with the biology of these viruses: typically, IV infections predominantly involve the upper respiratory tract and trachea [18,19], as human strains of IV primarily target cells of the upper airway [20], unlike RSV infections, which are more commonly associated with lower respiratory tract infections such as bronchiolitis and pneumonia [21,22].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Cough was the most frequently reported symptom, associated with IV, RSV and HMPV detections, as expected [1,3,17]. Presence of dyspnoea was associated with RSV infection and absence of dyspnoea was related to IV detection, as previously reported [16]. This is consistent with the biology of these viruses: typically, IV infections predominantly involve the upper respiratory tract and trachea [18,19], as human strains of IV primarily target cells of the upper airway [20], unlike RSV infections, which are more commonly associated with lower respiratory tract infections such as bronchiolitis and pneumonia [21,22].…”
Section: Discussionsupporting
confidence: 83%
“…The clinical signs associated with detection of a virus among patients with S-ILI varied among age groups. However, differences in age-related clinical symptoms should be interpreted cautiously, as the frequency of the four isolated viruses differed markedly among children and adults [4,16]. Consequently, the limited number of individuals for some age-subgroup analyses could explain in part the age-related differences in clinical signs highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Although the SARI case definition showed a good association with influenza in this study, it is noteworthy that influenza was still identified in 3% of non‐SARI cases. It has been shown before that influenza case definitions are highly age‐dependant and performances vary due to the unspecific clinical picture of influenza . Hence, laboratory‐based surveillance systems using a SARI definition will probably underestimate the true burden of influenza infections.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in previous research, ILI represents a good proxy for influenza estimates [3, 24]. As no influenza virological confirmation was available, we took only into account ILI occurring during the influenza epidemic period identified by the Sentinelles network.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical manifestations occur through influenza-like-illness (ILI) with sudden onset of fever, myalgia and respiratory signs [3]. …”
Section: Introductionmentioning
confidence: 99%